Analisis Latihan Soal Bahasa Arab pada Buku Ajar Mahir fi Lughoh Arabiyah Perspektif Taksonomi Bloom - Maghfiroh, Rodiatul; Amrullah, Abdul Malik Karim; Wahidmurni, Wahidmurni; Anwar, Mohammad Shohibul (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2024)
This study aims to analyze the practice questions contained in the textbook "Mahir fi Lughoh Arabiyah" using Bloom's taxonomic approach. This approach is used to evaluate the level of thinking and understanding of students tested through practice questions. The analysis method is carried out by categorizing the problems in the textbook into six levels of Bloom's taxonomy, namely knowledge, understanding, application, analysis, synthesis, and evaluation. The results of the analysis show that the textbook "Mahir fi Lughoh Arabiyah" has successfully implemented Bloom's taxonomic approach well. The practice questions in the textbook cover different levels of taxonomy, from basic knowledge of Arabic vocabulary and grammar to students' ability to apply and analyze authentic Arabic texts. The study concluded that the textbook "Mahir fi Lughoh Arabiyah" had adopted Bloom's taxonomic approach well in designing practice problems. By covering various levels of taxonomy, this textbook is able to encourage students' thinking and understanding in learning Arabic. The recommendation of this study is the importance of using Bloom's taxonomy in designing practice problems to improve the effectiveness of Arabic learning in higher education.